Pendampingan dan Sosialisasi Perizinan Berusaha berbasis Risiko pada Pengusaha dan Sopir Angkutan Barang Umum di Kota Baubau - Mahdar; Satyadharma, Maudhy (LPPM UNIVERSITAS LANCANG KUNING, 2024)
The transportation sector has become an important requirement in encouraging the movement of people and goods and has implications for the economic development of a region. Organizing Goods Transportation is one of the driving forces in the distribution of goods and logistics from one region to another, but unfortunately many elements are ignored in this implementation, including business licensing. This encourages the need for assistance and outreach regarding Public Goods Transportation business licensing to many business actors and this activity was chosen in Baubau City. Socialization was carried out and aimed at Transport Legal Entities, especially Public Goods Transport and Public Goods Transport drivers in Baubau City. The results of the mentoring and socialization carried out have encouraged an increase in better understanding among Public Transport drivers and Legal Entities about what transportation business licensing, especially Public Goods Transport is like, so that it is hoped that awareness will arise to process permits in accordance with applicable regulations.